Peroxidase activity in Malpighian tubules of Triatoma infestans Klug - Oliveira, Maria Tercília Vilela de Azeredo [UNESP]; Mello, MLD (Faculty Press, 1998)
Benzidine and diamino benzidine (DAB) oxidation, typically performed by peroxidases, was demonstrated by light and electron microscopy in peroxisomes, mitochondria and membranous structures which occurred in close contact with urate crystals in Malpighian tubules of nymphs and adults of Triatoma infestans. Peroxisomes were predominantly identified in cells of the distal region of the tubules, which is engaged in excretory mechanisms. DAB oxidation in mitochondria, even in the absence of hydrogen peroxide, may indicate the existence of a mitochondrial peroxidase and possibly a cytochrome c peroxidase. The localization of the extracellular membranous structures appeared restricted to the lumen of the proximal region of the tubules and they were assumed to be remnants of endoplasmic reticulum containing peroxidases.
Keywords: peroxidases; Malpighian tubules; Triatoma infestans; DAB oxidation; laminated concretions; peroxisomes